2020
DOI: 10.14740/jocmr4144
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Assessment in Patients on Moderate- or High-Intensity Statin Therapy

Abstract: Background: Cardiovascular diseases are the leading cause of death in the USA. Statin therapy reduces cardiovascular events significantly. Cognitive impairment has been reported with statin therapy but there is a lack of consensus. We analyzed the cognitive functions of adult patients who were on moderate-intensity statin therapy (MIST) or high-intensity statin therapy (HIST). Methods:A total of 213 patients underwent cognitive assessment testing. Cognitive function scores were correlated with the durations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The only caveat is emerging from work implicating lower cholesterol level in decreasing central serotonergic neurotransmission with effect on cognitive performance, mood, and impulsive behavior, which may influence the clinical course of the psychiatric condition present in our sample. 19 The effect seems to be more prominent in patients treated with the lipophilic statins atorvastatin and simvastatin. 20 A similar framework may also seem reasonable regarding the observed better control of diabetes in our dementia sample.…”
Section: Discussionmentioning
confidence: 99%
“…The only caveat is emerging from work implicating lower cholesterol level in decreasing central serotonergic neurotransmission with effect on cognitive performance, mood, and impulsive behavior, which may influence the clinical course of the psychiatric condition present in our sample. 19 The effect seems to be more prominent in patients treated with the lipophilic statins atorvastatin and simvastatin. 20 A similar framework may also seem reasonable regarding the observed better control of diabetes in our dementia sample.…”
Section: Discussionmentioning
confidence: 99%
“…The association frequency of T2D was significantly higher in the patients on High-Intensity Statin Therapy (HIST) with cognitive impairment in comparison with patients without cognitive impairment. There was no difference in the frequency 10.3389/fnagi.2022.968039 of association of T2D in the patients on Moderate-Intensity Statin Therapy (MIST) with or without cognitive impairment (Roy et al, 2020). Nevertheless, it has been suggested that the benefits of statin use in the prevention and treatment of CVD outweigh the possible adverse effects of statins on cognitive aging associated with T2D (Offer et al, 2019).…”
Section: Diabetesmentioning
confidence: 99%
“…A randomized controlled trial on older adults with hypertension showed that long-term use of 10 mg rosuvastatin may reduce WMH progression and cognitive impairment (Zhang et al, 2019). * Harmful HIST (atorvastatin 40-80 mg, rosuvastatin 20-40 mg) was associated with a higher frequency of cognitive impairment compared to MIST (atorvastatin 10-20 mg, rosuvastatin 10 mg, simvastatin 20-40 mg, and pravastatin 40-80 mg) (Roy et al, 2020).…”
Section: Protectivementioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore highly questionable to use cholesterol-lowering as treatment of people or patients with FH, also because it is well-known that statin treatment has many serious side effects [ 57 ]. The commonest one is considered to be muscular damage, but it is little known that many types of cerebrospinal dysfunction may occur as well, both in mice [ 58 ] and human beings [ 57 , 59 , 60 , 61 ]. They include cognitive dysfunction, suicidal or violent behavior, memory loss, Alzheimer’s, aphasia, polyneuropathy, and many others.…”
Section: The Contradictionsmentioning
confidence: 99%